Silver nitrate therapy for persistent tracheocutaneous fistula following prolonged tracheostomy and invasive ventilation: A case report. Issue 11 (21st October 2022) - Sweeney, Duncan J.; Chao, Caroline; Ridgers, Anna; Knee Chong, Christine; Goldblatt, Joshua; Seevanayagam, Siven; Howard, Mark E.
Abstract: We report the case of a man with severe Guillain‐Barré syndrome who developed a persistent tracheocutaneous fistula (TCF) following prolonged tracheostomy and mechanical ventilation. Following tracheostomy decannulation, the TCF had a deleterious effect on non‐invasive positive pressure ventilation efficacy and ability to effectively clear airway secretions due to air leaking from the patent stoma. This case highlights a non‐surgical approach to TCF management that is not well‐described in the literature and presents an alternative management option for cohorts of patients in which the risk associated with surgical interventions may be undesirable. Abstract : Most published management strategies of tracheocutaneous fistulas typically focus on surgical approaches. However, in certain scenarios such as patients with respiratory insufficiency or chronic respiratory failure, surgical management poses an unacceptable perioperative risk. This case highlights a non‐surgical approach to TCF management that is not well‐described in the literature and presents an alternative management option for cohorts of patients in which the risk associated with surgical interventions may be undesirable.